Symbolism and regime change in Russia - Gill, Graeme J. (Cambridge University Press, 2013)
Regime change in Russia has not been accompanied by a coherent new system of political symbolism. Following the fall of the Soviet regime, no single symbolic programme has emerged to replace the Soviet version. Gill investigates why and examines the symbolism that in fact emerged.